Joy in service on Rue Tagore - Muldoon, Paul 1951- (Farrar, Straus and Giroux, 2024)
"Since his 1973 debut, New Weather, Paul Muldoon has created some of the most original and memorable poetry of the past half century. Joy in Service on Rue Tagore sees him writing with the same verve and distinction that have consistently won him the highest accolades. Here, from artichokes to zinc, Muldoon navigates an alphabet of image and history, through barleymen and Irish slavers to the last running wolf in Ulster. The search involves the accumulated bric-a-brac of a life, and a reckoning along the way of gains against loss. In the poet's skillful hands, ancient maps are unfurled and brought into focus--the aggregation of Imperial Rome and the dismantling of Standard Oil, the pogroms of a Ukrainian ravine and of a Belfast shipyard. Through modern medicine and warfare, disaster and repair, these poems are electric in their energy, while profoundly humane in their line of inquiry." -- Dust jacket flap
Keywords: Irish poetry; English poetry / Irish authors; Poetry, Modern